2021
DOI: 10.1002/biot.202100431
|View full text |Cite
|
Sign up to set email alerts
|

Targeting metabolic driving and minimization of by‐products synthesis for high‐yield production of D‐pantothenate in Escherichia coli

Abstract: Background: D-Pantothenate (DPA) is an important functional chemical that has been widely applied in healthcare, cosmetics, animal food, and feed industries. Methods and Results:In this study, a high-yield DPA-producing strain was constructed by metabolic engineering strategies with targeting metabolic driving and by-products minimization. The metabolic driving force of push and pull was firstly obtained to improve the production of DPA via enrichment of precursor pool and synthetic pathway, accumulating 4.29 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 42 publications
(65 reference statements)
0
11
0
Order By: Relevance
“…The targeting gene and vector backbones were ligated using ClonExpress. 52 The primers used in this study are shown in Table S1.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…The targeting gene and vector backbones were ligated using ClonExpress. 52 The primers used in this study are shown in Table S1.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…The culture conditions were implemented as described in our previous study. 52 For fedbatch fermentation, the fermentation medium contained 20 g/ L glucose, 16 g/L (NH 4 ) 2 SO 4 , 2 g/L yeast extract, 2 g/L KH 2 PO 4 , 0.5 g/L MgSO 4 , 0.5 g/L betaine, and 1 mL/L essential metal salt solution. In the process of fed-batch fermentation, DO was maintained at 20%.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
See 3 more Smart Citations